Aryl-triazole foldamers with ethynyl spacers as effective receptors for halides and oxyanions. Issue 15 (13th April 2016) - Zhao, Wei; Huang, Fu; Wang, Ying; Li, Qiaolian; Shang, Jie; Che, Yanke; Jiang, Hua
Graphical abstract: Highlights: A new aryl-triazole receptor incorporating ethynyl spacer was readily constructed. These receptors bind various anions with high affinities but a low selectivity. These results may provide a new application of anion abstraction in sewage treatment. Improve our insights into anion binding properties and design novel anion receptors. Abstract: A new aryl-triazole receptor incorporating ethynyl spacer was readily constructed. By using UV–Vis spectroscopic titration, the foldamers were proved to be capable of binding various shaped anions ( n Bu4 N + A −, A = Cl, Br, I, NO3, HSO4, H2 PO4 and AcO) with high affinities but a low selectivity.